Cystatin C sebagai Biomarker Fungsi Ginjal: Literature Review - Pestalozi, George; Akbar, Fareel Wahyu; Ramadhian, Muhammad Ricky; Graharti, Risti; Lisiswanti, Rika (Medula, 2025)
Kidneys are the primary organs responsible for the excretion of metabolic waste products. Glomerular Filtration Rate (GFR) serves as a critical parameter for assessing renal function, with serum creatinine traditionally utilized as the primary biomarker. However, the accuracy of creatinine-based assessments is limited by its susceptibility to external variables, including age, sex, muscle mass, and dietary intake. These factors can lead to variability in results and reduce diagnostic precision. To overcome these limitations, cystatin C (CysC) has gained prominence as a superior alternative biomarker. Unlike creatinine, serum CysC levels are minimally influenced by external factors, offering greater stability and sensitivity in detecting acute kidney injury (AKI), chronic kidney disease (CKD), and other renal impairments such as diabetic nephropathy. Cystatin C provides notable advantages in the reclassification of CKD stages, particularly in cases where GFR measurements are borderline. CysC has demonstrated superior reliability over creatinine in predicting complications such as delayed graft function (DGF), a condition often necessitating hemodialysis. Preoperative measurement of CysC levels is instrumental in predicting long-term renal function and identifying patients at elevated risk for adverse outcomes. Elevated serum CysC concentrations in patients with renal cell carcinoma (RCC) have been correlated with poorer prognoses and an increased likelihood of postoperative renal injury. Despite its clinical advantages, the routine adoption of CysC is constrained by certain limitations. Chief among these is the significantly higher cost of CysC assays compared to traditional creatinine tests, which restricts its widespread application to confirmatory diagnostics or complex clinical scenarios.